Purchasing power parity approach to exchange rate misalignment in Nigeria - Musa Nakorji; Ngozi T. I. Agboegbulem; Blessing A. Gaiya; Ngozi V. Atoi (CBN Journal of Applied Statistics, 2021)
This study examines the purchasing power parity (PPP) approach to the determination of exchange rate misalignment in Nigeria by using two variants of the PPP: the absolute PPP (aPPP) and the relative PPP (rPPP). Data on the Nigerian Naira to US Dollar (/), British Pound (/) and Chinese Yuan (/¥) interbank exchange rates, Nigeria consumer price index and Inflation as well as the US, UK and China consumer price indices and inflation rates spanning 2008:M1 to 2018:M12 were utilized. A recently modified fractional cointegration framework was employed, taking care of smooth structural breaks and nonlinearity, while the unit root tests employed the fractional alternatives. The results confirmed that the aPPP approach to exchange rate determination is unrealistic but revealed empirical support for the rPPP approach. Furthermore, the exchange rates computed with the rPPP approach show that the interbank Naira to US Dollar, UK Pounds and Chinese Yuan exchange rates were overvalued in most of the period of this study. The period of undervaluation observed in June 2016 and April 2017 coincided with the periods when CBN introduced the investors and exporters window. The study recommends the use of rPPP for gauging the level of exchange rate misalignment in Nigeria and suggests the need to diversify the export base to appreciate the exchange rate.
Keywords: C3; C5; C13; 330; Exchange rate; overvaluation; undervaluation; purchasing power parity